Main electronics chasis for Bendix Mass Spectrometer - Bendix Corporation (1971)
General view of the interior of the main electronics chasis (enclosure) for a Bendix Corporation MA-2 Time-of-Flight Mass Spectrometer. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Scientific apparatus and instruments; Mass spectrometers; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Spectrometer industry